Does the market value “green” companies? Evidence from Indonesia (Asian Journal of Economics and Business Management, 2023)
Financial reporting is important for disclosing crucial information that shows the financial activities and performance of a business. Environmental disclosure in the annual report will enable investors and other interested parties to make informed judgments about the efficiency and impact of managers' sustainability decisions and actions. The aim of this study is to knowledge whether the stock market value the company that are of environmental, by performance and self-disclosure. This study makes significant contributions to the literature in several aspects. First, this is the first study to empirically examine the value relevance of 2 types of non-financial performance that use evidence from Indonesia Stock Market, to the best of our knowledge prior study only use one types of environmental reputation, performance or disclosure itself. This study uses the Ohlson modification model, however, the price model developed by Ohlson in this study modified by adding environmental information as other information that is expected to affect share prices. The results of this study are that environmental performance is value relevant to share prices, which shows that environmental performance influence investors in positive side. Whereas sustainability report disclosure shows different results, the effect is negative towards share prices, these results indicate that companies with high levels of sustainability report disclosure are not highly valued by investors. This can be caused by investors lack of understanding the importance of sustainable companies.